Effect of intravenous lidocaine on ischemia-reperfusion injury in DIEP microsurgical breast reconstruction. A prospective double-blind randomized controlled clinical trial. Issue 4 (April 2021) - Del Rio, M.; Lopez-Cabrera, P.; Malagón-López, P.; Del Caño-Aldonza, MC.; Castello, JR.; Provencio, M.
Abstract: Background: Ischemia-reperfusion injury in free flaps is associated with tissue damage and is one of the main factors causing flap failure in reconstructive microsurgery. The aim of this study is to assess whether any ischemia-reperfusion injury takes place during a microsurgical flap reconstruction as seen through the levels of malondialdehyde (MDA) and superoxide dismutase, biomarkers of oxidative stress, and to analyze the effect of lidocaine in this process. Methods: Twenty-four patients operated for immediate breast reconstruction using the Deep Inferior Epigastric Perforator free flap technique were divided into two groups: one group was treated with a lidocaine intravenous perfusion and the other group with a saline perfusion. MDA and superoxide dismutase (SOD) levels were measured at several points before, during, and after surgery. Results: There was an increase in MDA levels in both groups, but the lidocaine group experienced a decrease during reperfusion. On the other hand, we observed a rise in SOD levels in both groups, but a decrease during reperfusion in the placebo group. However, these differences between groups were not statistically significant. Conclusions: The decreased SOD activity and increased MDA content in our research prove a redox imbalance and high reactive oxygen species levels in flaps, indicating that tissues experience ischemia-reperfusion injury during microsurgical reconstruction. Lidocaine may have a protective effect in free flap surgery, but our results were not statistically significant, so further studies will be required.